Papillary Thyroid Microcarcinoma: Active Surveillance Against Surgery. Considerations of an Italian Working Group From a Systematic Review - Orlando, Giuseppina; Scerrino, Gregorio; Corigliano, Alessandro; Vitale, Irene; Tutino, Roberta; Radellini, Stefano; Cupido, Francesco; Graceffa, Giuseppa; Cocorullo, Gianfranco; Salamone, Giuseppe; Melfa, Giuseppina (Frontiers in Oncology, 2022)
Introduction: Active surveillance is considered a viable option for papillary thyroid microcarcinoma. Since the last decade of the 20th century, this method has spread from Japan to other countries, but has not yet been fully accepted and validated by the major Western Scientific Societies. In 2016, a systematic review on the results of active surveillance was published, based on two articles that showed encouraging results. Other reviews published subsequently, were mainly based on articles from the Far East. The aim of this review is to assess the most recent results published from 2017 to 2021 on this subject. Materials and Methods: A systematic literature search was performed on MEDLINE via PUBMED, Web of Science, and Scopus according to PRISMA criteria. The MESH terms "papillary thyroid microcarcinoma" and "active surveillance" were adopted. Tumor progression, secondary localizations, and quality of life were the main benchmarks. Results: Nine studies met the inclusion criteria. The increase in volume ranged from 2.7% and 23.2%; the occurrence of lymph node metastases from 1.3% to 29%; QoL was improved in both articles that addressed this topic. The level of evidence is considered low due to the retrospective and uncontrolled nature of most of the studies included in the review. Conclusion: The evidence from the literature currently available on AS falls into two strands: a robust data set from the Japanese experience, and an initial experience from Western countries, whose data are still limited but which show a lack of substantial alerts against this practice. Further data is useful to validate the spread of Active Surveillance.